FAKTOR DOMINAN YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA DI AKADEMI KEPERAWATAN WILLIAM BOOTH SURABAYA - ., Ethyca Sari, Yuliana Sedin (S1 Keperawatan, 2013)
Learning achievement is the end result in person and used to achieve success during sebaga ikuran enrolled in a school. Based on the observations of the author in Akademi Keperawatan William Booth Surabaya students who receive optimal learning achievement with a cumulative GPA â¥ 3.00 start first semester - VI only achieved by the same students. This is caused by various factors. Factors affecting the achievement of physiological factors, psychological factors, family support factors, environmental factors, school, community environmental factors. The purpose in doing this study is to mengidantifikasi dominant factor affecting student achievement in Akademi Keperawatan William Booth Surabaya. The design of this study "descriptive". Population of 27 people, with a sampling technique that is in use "Total Sampling" and the data collected by questionnaires then the data in manually though. Based on the results of research on the physiological factors memepengaruhi get that achievement of students in the Academy of Nursing William Booth Surabaya as many as 27 people (100%), psychological factors as many as 27 people (100%), most of the family support factor 14 people (52%), environmental factors most of the 18 schools (67%), the environmental factors 1 (4%), and the dominant factor affecting student achievement in Akademi Keperawatan William Booth Surabaya is the physiological factors and psychological factors as many as 27 people (100%). This is caused because the optimal achievement can be obtained if there is a desire and spirit of the individual or the students themselves. The desire and the spirit must be supported by a stable physical condition and psychological health.Keywords : physiological factors, psychological factors, factors of family support, school environment factors, environmental factors, community, academic achievement.